1996
DOI: 10.1161/01.res.79.3.541
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Collagen Turnover Following Experimental Balloon Angioplasty Injury and the Role of Matrix Metalloproteinases

Abstract: Extracellular matrix formation is the major component of the restenosis lesion that develops after balloon angioplasty. Although ex vivo studies have shown that the synthesis of collagen is stimulated early after balloon angioplasty, there is a delay in accumulation in the vessel wall. The objectives of this study were to assess collagen turnover and its possible regulation by matrix metalloproteinases (MMPs) in a double-injury iliac artery rabbit model of restenosis. Rabbits were killed at four time points (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
107
1
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(118 citation statements)
references
References 52 publications
9
107
1
1
Order By: Relevance
“…[12][13][14][15] We believe that our experiments represent the first characterization of the expression of elastolytic cathepsins and their inhibitor in the rat carotid artery balloon-injury model.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…[12][13][14][15] We believe that our experiments represent the first characterization of the expression of elastolytic cathepsins and their inhibitor in the rat carotid artery balloon-injury model.…”
Section: Discussionmentioning
confidence: 79%
“…7,8,11 However, previous observations have suggested that the even effective inhibition of MMPs and serine proteases might not sufficiently arrest neointima formation. [12][13][14][15] Cathepsins, lysosomal proteases within the papain superfamily, are thought to generally reside in and function optimally within acidic lysosomes. 16 Despite their lysosomal origin and optimal acidic pH, some of cathepsins including cathespin S and K can be secreted and retain a large portion of their proteolytic activity at neutral pH.…”
mentioning
confidence: 99%
“…Zymographic techniques are used for the detection of enzymatic activities. 11 We found that MMP-9 was associated with prostate cancer in tissue and serum specimens. We also detected a change in the ratio of the active form and proform of MMP-2 in prostate cancer.…”
Section: Introductionmentioning
confidence: 74%
“…The zymography was conducted according to established reports 11,13 with minor modifications. Briefly, fresh prostatic issues were cut into small pieces and mixed with ice-cold extraction buffer (50 mM Tris-HCl pH7.4, 1% NP-40, 150 mM NaCl, 1 mM EDTA).…”
Section: Zymographymentioning
confidence: 99%
“…18,19 For example, after arterial injury, TN-C and MMPs 20 are up-regulated during the development of occlusive neointimal lesions, whereas inhibition of MMP activity attenuates this process. 21 In addition, both MMP-2 22 and TN-C 23,24 are able to bind the same cell surface receptor, the ␣v␤3 integrin, further indicating that their regulation and functions may be interdependent. In fact, we have recently shown that extracellular matrix protein proteolysis by MMPs activates TN-C transcription via an ERK1/2 MAPK-dependent signaling pathway.…”
mentioning
confidence: 99%